LEGAL MECHANISM OF PROTECTION OF RIGHTS OF MILITARY PERSONNEL IN UKRAINE DURING THE STATE OF MARTIAL - Varava, Irina; Cherevatiuk, Victoria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the research is to find effective and optimally possible legal mechanisms for the protection of the rights of military personnel in the conditions of martial law and military operations. Research methods: to achieve the defined goal, general and special scientific methods were used, in particular, dialectical, axiological, objectivity, systematic, analysis, and comparative legal methods. Results: legal and social protection of military men and their family members in the conditions of armed aggression of the Russian Federation against Ukraine is gaining special importance. The provisions of the national legislation, which have undergone changes in the context of the regulation of additional guarantees for persons who perform defense tasks in response to armed aggression, are clarified. Attention is focused on the relationship between the state of the country’s defense capability and the provision of enhanced legal and social protection of military personnel, conscripts or reservists. Discussion: according to the information of law enforcement agencies, the number of criminal proceedings regarding war crimes and illegal arms trafficking has increased to a record level. At the same time, the number of other pre-war proceedings has significantly decreased. Legislative changes and some aspects of the investigation of war crimes have a significant impact on solving the problem of violation of the rights of military men and making balanced and fair decisions. The authors raise the problem of protecting the rights of military personnel in a particularly difficult period of martial law and military operations. As a conclusion, it is noted that the provision of enhanced social protection of military personnel contributes to the fulfillment by citizens of Ukraine of their duty to protect the Motherland - Ukraine, its sovereignty, independence and territorial integrity. Establishing such an approach to the legal and social protection of military personnel becomes part of ensuring the country’s defense capability.